Seroprevalence of HIV, HBV, HCV and syphilis in blood donors in Southern Haryana - Arora Dimple; Arora Bharti; Khetarpal Anshul (Wolters Kluwer Medknow Publications, 2010)
Blood transfusion is an important mode of transmission of infections to recipients. The aim of the study was to assess the prevalence of transfusion-transmissible infections among blood donors. For this, a 3.5-year retrospective study, from October 2002 to April 2006 was conducted at the blood transfusion centre of Maharaja Agrasen Medical College, Agroha (Hisar) Haryana. Donors were screened for seroprevalence of HIV, HBV, HCV and syphilis. A total of 5849 donors were tested, out of which 4010 (68.6%) were replacement donors and 1839 (31.4%) were voluntary donors. The seroprevalence of HIV was 0.3% in the donors. No voluntary donor was found to be positive for HIV. The low sero-positivity among donors is attributed to pre-donation counseling in donor selection. The seroprevalence of HBV, HCV and syphilis was 1.7%, 1.0% and 0.9% respectively in total donors. The seroprevalence of hepatitis and syphilis was more in replacement donors as compared to voluntary donors.